2022
DOI: 10.1192/j.eurpsy.2022.2340
|View full text |Cite
|
Sign up to set email alerts
|

The association of kynurenine pathway metabolites with symptom severity and clinical features of bipolar disorder: An overview

Abstract: This peer-reviewed article has been accepted for publication but not yet copyedited or typeset, and so may be subject to change during the production process. The article is considered published and may be cited using its DOI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…depression and mania, than by the disease itself. [68][69][70] Potential neurobiological underpinnings of predominant polarity in bipolar disorder are also a matter for future research.…”
Section: Discussionmentioning
confidence: 99%
“…depression and mania, than by the disease itself. [68][69][70] Potential neurobiological underpinnings of predominant polarity in bipolar disorder are also a matter for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a non-linear relationship was detected where deviation from midline kynurenine concentrations in either direction was associated with more extreme neurological and dementia symptoms [ 149 ]. Kynurenine metabolites have also been linked to bipolar disorder, which is a complex neurological disorder that affects approximately 2% of the population [ 150 , 151 ]. Notably, recent meta-analyses have shown there is a connection between metabolites of the kynurenine pathway and bipolar disorder, but the mechanistic and possibly causative relationship remains less well understood [ 150 , 151 ].…”
Section: The Tryptophan Pathway: Microbial-derived Metabolic Mind Con...mentioning
confidence: 99%
“…Kynurenine metabolites have also been linked to bipolar disorder, which is a complex neurological disorder that affects approximately 2% of the population [ 150 , 151 ]. Notably, recent meta-analyses have shown there is a connection between metabolites of the kynurenine pathway and bipolar disorder, but the mechanistic and possibly causative relationship remains less well understood [ 150 , 151 ]. Though the causative relationship may not yet be fully elucidated, it is nevertheless clear that metabolites stemming from the kynurenine pathway play key roles as markers of disease or perhaps even causative agents.…”
Section: The Tryptophan Pathway: Microbial-derived Metabolic Mind Con...mentioning
confidence: 99%
“…However, some of this evidence has been mixed. For instance, a more recent review found that some features of BD, such as psychotic episodes and suicide attempts, may also be associated with an imbalance in kynurenine pathway metabolism, though this finding requires replication ( Bartoli et al, 2022 ). In addition, another recent meta-analysis of eight CSF studies found no evidence of increased KA levels or differences in TRP levels associated with BD ( Inam et al, 2023 ).…”
Section: The Immune-inflammatory Systemmentioning
confidence: 99%